Using Provider Performance Incentives to Increase HIV Testing and Counseling Services in Rwanda - de Walque, Damien; Gertler, Paul J.; Bautista-Arredondo, Sergio; Kwan, Ada; Vermeersch, Christel; de Dieu Bizimana, Jean; Binagwaho, Agnès; Condo, Jeanine (Elsevier, 2015)
Paying for performance provides financial rewards to medical care providers for improvements in performance measured by utilization and quality of care indicators. In 2006, Rwanda began a pay for performance scheme to improve health services delivery, including HIV/AIDS services. Using a prospective quasi-experimental design, this study examines the scheme's impact on individual and couples HIV testing. We find a positive impact of pay for performance on HIV testing among married individuals (10.2 percentage points increase). Paying for performance also increased testing by both partners by 14.7 percentage point among discordant couples in which only one of the partners is an AIDS patient.